1969
DOI: 10.2466/pms.1969.29.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Awakening Thresholds and Dream Recall in NREM Sleep

Abstract: Whereas earlier research had shown that Ss with lower auditory awakening thresholds (AATs) reported more dreams on awakenings from non-rapid eye movement (NREM) sleep, this study of 4 Ss over several nights each indicated no relationship between Stage 2 NREM dreaming and within-subject, within-night variations in AAT. Subjectively “deep” Stage 2 sleep was associated with high AATs and with reports of Stage 2 dreaming. AATs declined over successive nights of laboratory sleep. Earlier reports of similar AATs for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…As regards the significant decreasing linear trend of sleep inertia found for both dependent variables in the course of almost every experimental night~Table 2!, it is similar to that of auditory arousal thresholds assessed during the same nights~Ferrara et al, 1999b!. Auditory thresholds showed a linear overnight decrease that paralleled the fulfillment of sleep need, further supporting the existence of a time-of-night effect on auditory thresholds negatively related to the amount of accrued sleep~Rechtschaffen et al Watson & Rechtschaffen, 1969;Zimmerman, 1970!, keep-ing the sleep stage at awakening constant. This result again points out that performance upon awakening is mainly influenced by sleep depth.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…As regards the significant decreasing linear trend of sleep inertia found for both dependent variables in the course of almost every experimental night~Table 2!, it is similar to that of auditory arousal thresholds assessed during the same nights~Ferrara et al, 1999b!. Auditory thresholds showed a linear overnight decrease that paralleled the fulfillment of sleep need, further supporting the existence of a time-of-night effect on auditory thresholds negatively related to the amount of accrued sleep~Rechtschaffen et al Watson & Rechtschaffen, 1969;Zimmerman, 1970!, keep-ing the sleep stage at awakening constant. This result again points out that performance upon awakening is mainly influenced by sleep depth.…”
Section: Discussionsupporting
confidence: 63%
“…Auditory thresholds showed a linear overnight decrease that paralleled the fulfillment of sleep need, further supporting the existence of a time-of-night effect on auditory thresholds negatively related to the amount of accrued sleep~Rechtschaffen et al Watson & Rechtschaffen, 1969;Zimmerman, 1970!, keep-ing the sleep stage at awakening constant. This result again points out that performance upon awakening is mainly influenced by sleep depth.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Firstly, NREM ERPs were compared between the first and second halves of the night. It was reported that the auditory arousal thresholds during sleep were decreasing across the night, with increasing of frequency of awakening by auditory stimuli (Busby et al, 1994;Rechtschaffen et al, 1966;Watson and Rechtschaffen, 1969;Williams et al, 1964;Zimmerman, 1970). It indicates an elevation of arousal process or a reduction of inhibitory process to auditory inputs during the second part of the night when sleep drive has been partially satiated.…”
Section: Introductionmentioning
confidence: 94%
“…Although this response occurs spontaneously i.e., in the absence of disruptive external stimuli, it has been largely through the application of external stimuli in studies determining arousal thresholds from sleep that this process has been examined. These studies have considered varying degrees of arousal, ranging from subawakening variations in physiologic measures to indices of more complete arousal, such as specific behavioral responses indicating stimulus awareness (2,16,22,27), and have established the relevance of several stimulus (modality, intensity, and significance) and state (sleep stage and time of night) variables to the awakening process (18,24,26,39,40,41). In man, these studies have been carried out almost exclusively in adults, and those which have involved children (20,31,33) have not assessed the stimulus parameters required to elicit a behavioral response.…”
Section: Abbreviationsmentioning
confidence: 99%